Dimensional stability and mechanical properties of wood plastic composites produced from sawdust of anogeissus leiocarpus (ayin) with recycled polyethylene teraphthalate (pet) chips (2017)
Wood Plastic Composite panels were produced using a locally fabricated extruding machine at a temperature of about 170°C-200°C. the Sawdust of Anogeissus leiocarpus(Ayin) and Recycled Polyethylene Teraphthalate (PET) Chips were mixed in the ratio 1:1 to 1:5 and densities of 770.58 kg/mm3, 888.65 kg/mm3, 1,114.71 kg/mm3, 1,117.58 and 1, 141.84 kg/mm3 respectively. The quantity of recycled polyethylene teraphthalate (PET) Chips and sawdust used in the panels production were later weighed as 10 g of wood, 90 g of plastic; 8 g of wood, 92 g of plastic; 6 g of wood, 94 g of plastic; 4 g of wood, 96 g of plastic and 2 g of wood, 98 g of plastic. The components were mixed and fed into the extruder where they were melted, blended and consolidated. The material was then extruded through a die into a mould of dimensions 3.2 mm × 12.7 mm × 125 mm, 12.7 mm × 12.7 mm × 25.4 mm based on ASTM D 790 and ASTM D 695 for both flexural modulus and compression tests. It was observed that the test sample with woodplastic ratio 1:5 had the highest Impact Strength, MOR and MOE values of 42.33 J/m2, 3.86 N/mm2 and 642.00 N/mm2 respectively. Panels produced from mixing ratio 1:5 had the lowest values of 0.00 and 1.10% for both water absorption and thickness swelling respectively, while the specific gravity and density for the panel with mixing ratio 1:1 is the lowest with values 0.77 and 770.58 kg/m3 respectively, after 2 days or 48 hours immersion test. Analysis of variance showed that there were significant differences (Pr < 0.05) in all the physical and strength properties tests